Luppolo e “moral imagination” nella filiera moralmente controllata di Baladin - Damiano Cortese (Archivio Antropologico Mediterraneo)
Baladin is the pioneer producer and emblem of the Italian craft beer. Its “morally controlled supply chain” represents a sustainable model, in which innovation and economic success are rooted in the business ethics’ founding values. Hops, the plant characterizing beer, is one of the symbolic factors of corporate responsible choices with a positive and widespread impact: even in a market with a decreasing value its cultivation is the evidence of a strenuous position that guarantees a constant success. The business management perspective is aimed at bringing out replicable elements of a business that is emblematic from an environmental, economic, and social point of view.